Scum Sludge From Palm Oil Mill Effluent Treatment Plant As Biodiesel Feedstock - Gay, Benjamin (Universiti Sains Malaysia, 2021)
Biodiesel fuel has gain consumers attention as a more sustainable alternative for conventional non-renewable diesel fuel. Meanwhile, the management of floating scum on the surface of the palm oil mill effluent (POME) wastewater treatment lagoon has been an issue. In this study, the potential of using POME scum as biodiesel feedstock was investigated. The scum was collected from Hilltop Palms Sdn. Bhd. wastewater treatment pond and stored in a carboy container in a cold room. The characteristics of scum oil including viscosity, moisture content and acid value were determined. The moisture content in the scum was removed by oven drying at 105°C while the acid value was determined by titration of oil against potassium hydroxide standard solution. Then, the scum-to-biodiesel was produced through in-situ transesterification and the effects of operational parameters such as reaction time, catalyst dosage and solvent volume were studied. From the characterization of POME scum, the viscosity of the scum is negatively related to temperature, the average percentage of moisture content removed is 0.05% and the acid value of scum was reduced to less than 2 mg KOH/g oil through acid-catalysed esterification. The maximum scum-to-biodiesel yield percentage is 80.12% based on wet scum oil. The reaction condition for the maximum biodiesel yield percentage is the reaction of 10g wet scum oil dissolved in 70mL of n-hexane solvent aided by 5%wt H2SO4 acid catalyst (based on scum oil weight) in 100mL methanol at a reaction temperature of 60°C for 4 hours. From the FAMEs composition analysis, it was determined that the major component found in the biodiesel produced is methyl palmitate and methyl oleate which is also found in biodiesel produced from other vegetable oil. Therefore, POME scum has the potential for biodiesel production.